Multiple imaging and excellent anticancer efficiency of an upconverting nanocarrier mediated by single near infrared light. Issue 14 (23rd March 2017) - Wang, Yan; Yang, Guixin; Wang, Yanli; Zhao, Yanping; Jiang, Haizhi; Han, Yuyan; Yang, Piaoping
Abstract : It is difficult to meet the requirements of clinical diagnosis through a single imaging technique. Abstract : It is difficult to meet the requirements of clinical diagnosis through a single imaging technique. Similarly, satisfactory therapy efficacy is also hard to achieve by a single therapeutic modality. It is therefore highly desirable and interesting to simultaneously achieve multimodal imaging and therapies in one single structure. In this study, we developed a core–shell-satellite NaGdF4 :Yb, Er, Mn, Co@mSiO2 -CuS structure using up-conversion luminescent (UCL) NaGdF4 :Yb, Er, Mn, Co as the core, mesoporous silica as the layer, and the photoactive CuS nanoparticles as the satellites. The further linked photosensitizer (ZnPc) and doxorubicin hydrochloride (DOX) allow the system to have photodynamic therapy (PDT) and chemotherapy functions. The doping of Co 2+ ions in the core endows the carrier with T 2 -weighted magnetic resonance imaging (MRI) properties, and the co-doping of Mn 2+ ions can efficiently enhance the red emission which further improves the PDT efficiency by reacting with the attached ZnPc upon near-infrared (NIR) light irradiation. The nanoplatform exhibits excellent anti-tumor efficiency due to a synergistic effect arising from combined PDT, photo-thermal therapy (PTT) and chemotherapy, which has been evidenced by in vitro and in vivo results. Due to the multimodal imaging (MRI, CT, and UCL) properties, the drug delivery process and therapeutic efficacy can be monitored in real time and assessed, thus achieving the target of imaging-guided therapy.